2020
DOI: 10.1136/annrheumdis-2020-217419
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of canakinumab in patients with colchicine-resistant familial Mediterranean fever: results from the randomised phase III CLUSTER trial

Abstract: ObjectivesTo evaluate the long-term efficacy and safety of canakinumab to treat patients with colchicine-resistant familial Mediterranean fever (crFMF) during Epoch 4 (weeks 41 to 113) of the CLUSTER study.MethodsPatients received open-label canakinumab 150 or 300 mg, every 4 or 8 weeks during a 72-week period. We evaluated disease activity every 8 weeks using the physician global assessment (PGA) of disease activity, counting the number of flares, and measuring concentrations of C reactive protein (CRP) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 18 publications
4
33
0
2
Order By: Relevance
“…Substantial changes in median creatinine clearance values were not observed during the study and thus, it has not been elucidated whether canakinumab treatment can also prevent amyloidosis and renal complications. No SAEs were reported during the study period and in conclusion, the canakinumab treatment was shown to bear a potential of controlling disease in FMF patients as a long-term therapy ( 46 ).…”
Section: Familial Mediterranean Fevermentioning
confidence: 82%
See 1 more Smart Citation
“…Substantial changes in median creatinine clearance values were not observed during the study and thus, it has not been elucidated whether canakinumab treatment can also prevent amyloidosis and renal complications. No SAEs were reported during the study period and in conclusion, the canakinumab treatment was shown to bear a potential of controlling disease in FMF patients as a long-term therapy ( 46 ).…”
Section: Familial Mediterranean Fevermentioning
confidence: 82%
“…A CLUSTER study, a 16-week randomised phase III clinical trial with 72-week open-label period presented by Ozen et al ( 46 ) also measured the long-term treatment responses to canakinumab in colchicine-resistant FMF patients. In this 72-week long study, 61 patients were enrolled.…”
Section: Familial Mediterranean Fevermentioning
confidence: 99%
“…So liegen für den Einsatz von Rilonacept, Anakinra und Canakinumab bei Patienten mit hoher Krankheitsaktivität eines FMF trotz adäquat dosierter Kolchizin-Therapie mittlerweile publizierte Ergebnisse randomisierter kontrollierter Studien vor. Für Canakinumab gibt es auch bereits recht positive 72-Wochen-Daten [ 131 ].…”
Section: Diskussionunclassified
“…We read with great interest the article "Long-term efficacy and safety of canakinumab in patients with colchicine-resistant familial Mediterranean fever: results from the randomised phase III CLUSTER trial" by Özen et al 1 This article makes a remarkable contribution to treatment in patients with colchicineresistant familial Mediterranean fever (FMF), which shows a great remission rate with minimal side effects. However, there are some aspects that need to be clarified and discussed.…”
mentioning
confidence: 99%